PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA SOUTHLINKS COUNTRY CLUB BATAM - Kartini, Kartini; Hikmah, Hikmah (SCIENTIA JOURNAL, 2019)
Human_resources_are very_important for_an organization,_because human resource factors can not be replaced by_any technology. Organization that have good human resource performance, usually fast ini achieving organization goals even faster than planned. While_organizations that have poor performance_human resources just the opposite will be difficult to develop not able to follow the rapid progress. This research aims to test and analyze_the effect of motivation_and work environment on employee performance on Southlinks Country Club Batam, the population in this study consisted of 134 employees. Sampling_sample uses saturated sampling, the data collection method is by distributing questionnaires. The data_obtained by analysis using SPSS_version 25. The Analysis_data used is the classic assumption test which consists of the normality test, heteroscedasticity test, multicollinearity test. The influence test used in this study is a linear regression analysis .The results_of this_study are: motivation (X1) has a positive and significant effect on employee performance, work environment (X2) has a positive and significant effect on employee performance. From the results of the F_dapat_test it is known that motivation (X1) and work environment (X2) simultaneously_ positive and significant effect on employee performance.